Employee Competence and Attachment Impact against Employee Performance at PT.Vincent Sheppard Indonesia - Firda Sari, Santi; kartono, kartono; Sunimah, Sunimah (Jurnal Ekuisci, 2023)
Employee performance is significant to note since employees are crucial to the organization'sability to achieve its objectives and advance to compete successfully. Organizations or businesses withhigh employee performance will have more human resources available. Competence and employeeengagement are two elements that must be considered while attempting to improve employeeperformance. Competence is a characteristic that aids in achieving strong performance, and employeeengagement is a feature that employees receive for what they accomplish or obtain, with the desires ofemployees being met to ensure high motivation and morale at work. This study sought to ascertain howcompetency and employee engagement impacted workers' performance at PT. Vincent SheppardIndonesia. A quantitative research method was adopted for the study. The 275 participants in this studywere all PT. Vincent Sheppard Indonesia employees. The Slovin method was used in this investigationwith a 74-person sample and a tolerance level or error of 10%. The proportionate stratified randomsampling approach is the one that is employed. Multiple linear regression is the method of data analysisthat has been applied. The findings indicated that the factors of competence and employee engagementhad a favorable and significant impact on employee performance, either partially or concurrently.